Role of MR-DWI and MR-PWI in the radiotherapy of implanted pulmonary VX-2 carcinoma in rabbits - Zhang, Qiang; Zhang, Mingmin; Liu, Zhaoxin; Shi, Baoqi; Qi, Fuliang; Wang, Haijiang; Lv, Yuan; Jin, Haijiao; Zhang, Weijing (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To detect the activity of tumor cells and tumor blood flow before and after the radiotherapy of implanted pulmonary VX-2 carcinoma in rabbit models by using magnetic resonance diffusion-weighted imaging (MR-DWI) and magnetic resonance perfusion weighted imaging (MR-PWI), and to evaluate the effectiveness and safety of the radiotherapy based on the changes in the MR-DWI and MR-PWI parameters at different treatment stages. Methods: A total of 56 rabbit models with implanted pulmonary VX-2 carcinoma were established, and then equally divided into treatment group and control group. MR-DWI and MR-PWI were separately performed using a Philips Acheiva 1.5T MRI machine (Philips, Netherland). MRI image processing was performed using special perfusion software and the WORKSPACE advanced workstation for MRI. MRDWI was applied for the observation of tumor signals and the measurement of apparent diffusion coefficient (ADC) values; whereas MR-PWI was used for the measurement of wash in rate (WIR), wash out rate (WOR), and maximum enhancement rate (MER). The radiation treatment was performed using Siemens PRIMUS linear accelerator. In the treatment group, the radiotherapy was performed 21 days later on a once weekly dosage of 1,000 cGy to yield a total dosage of 5,000 cGy. Results: The ADC parameters in the region of interest on DWI were as follows: on the treatment day for the implanted pulmonary VX-2 carcinoma, the t values at the center and the edge of the lesions were 1.352 and 1.461 in the treatment group and control group (P>0.05). During weeks 0-1 after treatment, the t values at the center and the edge of the lesions were 1.336 and 1.137 (P>0.05). During weeks 1-2, the t values were 1.731 and 1.736 (P